First-line usage of daratumumab, lenalidomide, dexamethasone (DRd) combination in a case of castleman disease variant of polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, and skin changes syndrome (CD-POEMS) - Sevindik, Ömür Gökmen; Mutlu, Yaşa Gül; Balık Aydın, Berrin; Serin, İstemi (Lippincot Williams & Wilkins, 2022)
Polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, and skin changes syndrome (POEMS) is a rare paraneoplastic syndrome of an underlying plasma cell disorder (PCD).1 Castleman disease (CD), itself, can also cause symptoms or signs of polyneuropathy, volume overload, cytokine release, but only those with peripheral neuropathy and a plasma cell clone can be classified as classical POEMS.
Keywords: Skin Changes Syndrome (CD-POEMS); Endocrinopathy; Organomegaly; Monoclonal Gammopathy; Case of Castleman Disease